Late cytomegalovirus infection after hematopoietic stem cell transplantation: case reports - Pinheiro,Samara Grapiuna (2013)
Cytomegalovirus is related to high rates of morbidity and mortality after hematopoietic stem cell transplantation. This report highlights the importance of adequate monitoring and management of this infection. We report on two cases of patients with late subclinical cytomegalovirus infection. These patients were monitored for antigenemia by indirect immunofluorescence assay. Active cytomegalovirus infection is most common in the first three months after transplantation however the cases reported herein show the importance of monitoring for active infection after Day +100 post-transplantation. Early detection of active infection enables quick preemptive therapy. In conclusion, we emphasize that patients with risk factors for developing severe or late cytomegalovirus disease should be monitored for more than 100 post-transplant days as late active infection is a reality.